Psychological impact of the COVID-19 pandemic on patients with allergic diseases - González Díaz, Sandra Nora; Martin, Bryan; Villarreal González, Rosalaura Virginia; De Lira Quezada, Cindy Elizabeth; Macouzet Sánchez, Carlos; Macías Weinmann, Alejandra; Guzmán Avilán, Rosa Ivett; García Campa, Mariano; Noyola Pérez, Andrés; García González, David Uriel (Lippincott Williams & Wilkins, 2021)
On March 2020, WHO declared COVID-19 as a pandemic disease. Interactions between allergy-related inflammatory and psychiatric disorders including depression, anxiety and posttraumatic stress disorder (PTSD) have been documented. Therefore, those who have pre-existing allergic conditions may have an increased psychiatric reaction to the stresses of the COVID-19 pandemic.